WebSphere Portal V5.0 production deployment and operations guide - Credle, Rufus (IBM redbooks., 2005)
This IBM Redbooks publication contains best practices for deployment and operational support of WebSphere Portal V5 in a production environment. It addresses the questions on how to initially deploy WebSphere Portal. After you have deployed WebSphere Portal, you can use the operational best practices described in this book for themes, skins, pages, and portlet updates in a 24/7 enterprise. This book discusses the common notations for WebSphere Portal operational architecture and terminology. The architectures described in this book are examples used to present WebSphere Portal operation alternatives that allow you to combine, mix, and define your own Portal architecture. Portal administrators can find in this book an installation roadmap that includes a suggested approach, best practices, links to required resources, and hints to perform a successful installation and configuration. When the staging environment has been set, this book also provides helpful instructions on moving Portal into production. Please note that the additional material referenced in the text is not available from IBM.